Digoxin, mortality, and cardiac hospitalizations in patients with atrial fibrillation and heart failure with reduced ejection fraction and atrial fibrillation: An AF-CHF analysis. (15th August 2020) - Elayi, Claude Samy; Shohoudi, Azadeh; Moodie, Erica; Etaee, Farshid; Guglin, Maya; Roy, Denis; Khairy, Paul; ,
Abstract: Background: Recent publications have raised serious concerns regarding the safety of digoxin for atrial fibrillation (AF). However, the subgroup of patients with reduced ejection fraction and AF have been speculated to derive clinical benefit from digoxin. We aimed to assess the impact of digoxin on mortality and cardiovascular hospitalizations in the Atrial Fibrillation and Congestive Heart Failure (AF-CHF) trial since all AF-CHF patients had an ejection fraction ≤35% and AF. Methods and results: Using marginal structural modeling, a contemporary statistical method that overcomes limitations of traditional modeling techniques and reduces bias, we assessed the impact of digoxin on the pre-specified primary and secondary outcomes of the AF-CHF trial, i.e., all-cause, cardiac and arrhythmic death as well as cardiovascular hospitalization. Among 1376 patients, 869 (65%) were on digoxin at one-year follow-up. Over a mean (SD) follow-up of 37 (19) months (maximum 74 months), 445 (32%) patients died, 357 (26%) from cardiovascular causes and 159 (12%) from arrhythmic death. Digoxin was significantly associated with all-cause, cardiac, and arrhythmic death, with estimated hazard ratios (HR) of 1.39 (95% confidence interval [CI] 1.11–1.73, P = 0.004), 1.44 (95% CI 1.13–1.82, P = 0.003), and 2.03 (95% CI 1.63–2.54, P < 0.0001), respectively. Digoxin was not associated with cardiovascular hospitalizations [HR 1.12 (95% CI 0.91–1.37), P = 0.29]. Conclusion: Digoxin is associated with increased all-cause mortality among patients with combined heart failure with reduced ejection fraction and AF, which is predominantly driven by arrhythmic deaths. In contrast, cardiovascular hospitalizations were not impacted by digoxin. Highlights: Digoxin is associated with increased mortality among patients with combined HFrEF and AF. There was a particularly large increase in arrhythmic deaths. Cardiovascular hospitalizations were not impacted by digoxin. These compelling results call into question current guidelines regarding digoxin use among patients with AF and HFrEF.